Pilot Testing of an Information Extraction (IE) Prototype for Legal Research - Scholtz, Brenda; Padayachy, Thashen; Adewoyin, Oluwande (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2020)
This article presents findings from pilot testing of elements of an information extraction (IE) prototype designed to assist legal researchers in engaging with case law databases. The prototype that was piloted seeks to extract, from legal case documents, relevant and accurate information on cases referred to (CRTs) in the source cases. Testing of CRT extraction from 50 source cases resulted in only 38% (n = 19) of the extractions providing an accurate number of CRTs. In respect of the prototype’s extraction of CRT attributes (case title, date, journal, and action), none of the 50 extractions produced fully accurate attribute information. The article outlines the prototype, the pilot testing process, and the test findings, and then concludes with a discussion of where the prototype needs to be improved.
Keywords: information retrieval (IR), information extraction (IE), natural language processing (NLP), legal cases, document databases, source cases, cases referred to (CRTs)